Urban-agricultural water appropriation: the Hyderabad, India case - Celio, Mattia; Scott, Christopher A.; Giordano, Mark (Wiley, 2010)
With the urbanisation drive comes steady growth in urban water demand. Although in the past this new demand could often be met by tapping unclaimed water sources, this option is increasingly untenable in many regions where little if any unclaimed water remains. The result is that urban water capture, and the appropriation of associated physical and institutional infrastructure, now often implies conflict with other existing uses and users. While the urbanisation process has been studied in great depth, the processes and, critically, impacts of urban water capture and appropriation are not well researched or understood. This paper undertakes a critical examination of the specific case of Hyderabad, one of India's fastest growing cities, to shed light more generally on the process of water capture by cities and the resultant impacts on pre-existing claims, particularly agriculture. It does this by examining the history and institutional response to Hyderabad's urban-rural water contest; how the results of that contest are reflected in surface and groundwater hydrology; and the eventual impacts on agriculture. The findings show that the magnitude, and sometimes even direction, of impact from urban water transfer vary in space and time and depend on location-specific rainfall patterns, the nature of existing water infrastructure and institutions, and farmers' adaptive capacities and options, notably recourse to groundwater. Broader consideration of the specific findings provides insights into policy mechanisms to reduce the possible negative impacts from the global, and seemingly inexorable, flow of water to the world's growing cities.